Biometrics for Network Security - Reid, Paul (Prentice Hall series in computer networking and distributed systems., 2003)
The complete guide to implementing biometric security solutions for your network Network security has become the latter-day equivalent of oxymoronic terms like "jumbo shrimp" and "exact estimate." Newspaper headlines are routinely peppered with incidents of hackers thwarting the security put forth by the government and the private sector. As with any new technology, the next evolution of network security has long languished in the realm of science fiction and spy novels. It is now ready to step into the reality of practical application. In Biometrics for Network Security , biometrics security expert Paul Reid covers a variety of biometric options, ranging from fingerprint identification to voice verification to hand, face, and eye scanning. Approaching the subject from a practitioner's point of view, Reid describes guidelines, applications, and procedures for implementing biometric solutions for your network security systems. Coverage includes: An introduction to authentication technologies and biometrics Dealing with privacy issues Biometric technologies, including finger, hand geometry, handwriting, iris, retina, voice, and face Security concerns related to biometrics, including attempts to spoof or fake results Deployment of biometric security systems, including vendor selection and roll out procedures Real-life case studies For security, system, and network administrators and managers, as well as anyone who is interested in the application of cutting-edge biometric technology, Biometrics for Network Security will prove an indispensable addition to your library!